AYASOFYA I.MAHMUD KÜTÜPHANESİ VE GEÇİRDİĞİ ONARIMLAR - (:unkn) unknown (My University, 2015)
Sultan I.Mahmud tarafından yaptırılan eklentiler ile Ayasofyayı bir külliyeye çevirmiştir. Dönemi içinde şadırvan, sıbyan mektebi, imarethane ile birlikte bir de kütüphane inşa ettirmiştir. Kütüphanenin vakfiyesine göre 1740 tarihinde inşası tamamlanmış; açılışı Sultan I.Mahmudun katılımıyla aynı yılın nisan ayında yapılmıştır. Ayasofya I.Mahmud Kütüphanesi; mimarisi, kitap koleksiyonunun zenginliği ve geniş personel kadrosu ile önemli kütüphaneler arasındadır. Kütüphanede eğitimin düzenli hale getirilmiş, verilecek dersler vakfiyede belirlenmiş, öğrencilere ücret ödenmiştir Kütüphane yapısı, Ayasofyanın güney nefi üzerinde iki payanda arasına inşa edilmiştir. Mimari biçimlenme açısından diğer kütüphane yapılarından farklılık arz eder. Bir koridor üzerinde birbirine bağlanan giriş holü, okuma salonu, ışık taşlığı ve hazinei-i kütüb bölümlerinden oluşmaktadır. Giriş holü ile okuma salonu Ayasofya iç mekân içinde, hazine-i kütüb bölümü ise dışında kalmaktadır. Farklı mimari tasarımı ile ünik bir eser olarak değerlendirilebilinir. Mimari kurgusu ve kütüphaneciliğin, aynı zamanda eğitimin önemsendiği kütüphaneye ilişkin kısa bir tarihsel süreç ile ardından Osmanlı döneminde ve Cumhuriyet döneminde geçirdiği onarımlardan bahsedilmiş, ardından kapsamlı bir biçimde İstanbul İl Özel İdaresi ve İstanbul Rölöve ve Anıtlar Müdürlüğü kontrollüğünde, İstanbul Restorasyon ve Konservasyon Merkez ve Bölge Laboratuvarları Müdürlüğü raporları doğrultusunda yapılan 2012-2014 yılı restorasyonu anlatılarak değerlendirme yapılmıştır.

Hagia Sophia had been transformed into Islamic-Ottoman social complex in the period of Sultan Mahmud I, after the construction of new buildings. Sultan Mahmud I had built a library in addition to a fountain (sadirvan), a primary school, and an almshouse. According to the endowment, the construction of the library had completed in 1740; the library was opened in April, the same year with the participation of Sultan Mahmud I. Hagia Sophia Mahmud I Library was one of the important libraries of its era including its architecture, large collection of books and large personnel strength. The reasons that make the Library developed and became an important institution are; large collection of books, the lectures will be brought into regular education personnel working with determination in the endowment and the payment of wages in case of student attendance. Architecture of the Library; Library was built between two buttresses on the south nave of Hagia Sophia. This type of architecture differentiates Hagia Sophia Library from other libraries. The Library consists of entrance hall, reading hall, light stony ground and Hazine-i Kutub (place where the books were preserved) combining along a corridor. Entrance hall and reading hall with reticulate facade are located indoor; Hazine-i Kutub section is located outdoor of Hagia Sophia. Considering this different type of architectural design, the structure might be gradable as unique. In this article, an assessment is done by explaining the restoration in 2012-2013 after the brief historical process of the Library with its significant architectural type. The subject restoration was done in accordance with the reports of Istanbul Restoration and Conservation Center Laboratories and controlled by Istanbul Special Provincial Directorate of Administration and Istanbul Directorate of Surveying and Monuments.
Hagia Sophia Mahmud I Library and its Restorations
Keywords: Tarih